community-based education ANALISIS EMPIRIS TENTANG PENDIDIKAN DALAM KONTEKS MASYARAKAT TRADISIONAL, MODERN, DAN GLOBAL: ANALISIS EMPIRIS TENTANG PENDIDIKAN DALAM KONTEKS MASYARAKAT TRADISIONAL, MODERN, DAN GLOBAL - Nasrah Natsir; Latang; Febriansa; Muhammad Nur Alamsyah (Universitas Negeri Medan - Indonesia, 2026)
This study aims to determine how to improve the quality of education through the application of the Community Based Education model. A naturalistic qualitative approach is used in this study with data collection tools in the form of interviews, observations and documentation studies. The sample of this study is a number of junior high schools (MTs) located in Islamic Boarding Schools in Polewali Mandar. This study focuses on (1) how policies are taken by Islamic Boarding School Leaders and teaching staff in improving the quality of school education through the application of the Community Based Education model, (2) How is the program to improve the quality of Islamic Boarding School education by implementing the Community Based Education model. (3) How is the strategy for improving the quality of Islamic Boarding School education located in the application of high discipline. (4) What factors support the improvement of the quality of education. The results of the study show that the National Examination score experienced a jump in increase from an average of 6.96 to 6.98, and finally increased significantly to 7.69 in 2025 after the application of the community-based learning model.